2011
DOI: 10.1007/s10511-011-9178-5
|View full text |Cite
|
Sign up to set email alerts
|

Finite temperature calculations for the bulk properties of a strange star using a many-body approach

Abstract: We have considered a hot strange star matter, just after the collapse of a supernova, as a composition of strange, up and down quarks to calculate the bulk properties of this system at finite temperature with the density dependent bag constant. To parameterize the density dependent bag constant, we use our results for the lowest-order constrained variational (LOCV) calculations of asymmetric nuclear matter. Our calculations for the structure properties of the strange star at different temperatures indicate tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…We have calculated the thermodynamic properties and structure of SQS at finite temperature using MIT bag model with the fixed bag constant and density-dependent bag constant [18]. It has been shown that the EOS of the system in both cases (fixed bag constant and density-dependent bag constant) becomes stiffer by increasing temperature.…”
Section: Mass Of Sqsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have calculated the thermodynamic properties and structure of SQS at finite temperature using MIT bag model with the fixed bag constant and density-dependent bag constant [18]. It has been shown that the EOS of the system in both cases (fixed bag constant and density-dependent bag constant) becomes stiffer by increasing temperature.…”
Section: Mass Of Sqsmentioning
confidence: 99%
“…In recent years, we have investigated the thermodynamic properties of SQM and structure of SQS under different conditions using these frameworks. We have computed the structural properties of SQS at zero and finite temperatures, as well as the structure of a magnetized SQS using the MIT bag model with the fixed and density dependent bag constants at zero and finite temperatures in the presence and absence of magnetic fields [17][18][19][20][21]. We have also computed the maximum gravitational mass and other structural properties of a neutron star with a quark core at zero [22] and finite temperatures [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They investigated the thermodynamic properties and structure of cold polarized SQS [21,22] and the magnetized SQS at the finite temperature [23,24]. In addition, Non-polarized SQS using MIT bag model and NJL model have been investigated [25][26][27]. Furthermore, papers have been published to investigate properties of neutron stars with the quark core [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have applied the MIT bag model to investigate the cold and hot strange quark star. For example we consider MIT bag model with a density dependent bag constant for a hot strange star in [14], and found that the mass and radius of strange star decreases when temperature increases. We have also found that a higher mass and radius will be obtained for a density dependent bag constant compare to a fixed bag constant.…”
Section: Introductionmentioning
confidence: 99%